Prevalencia de Fasciola hepática en alpacas en la Comunidad Campesina Cahuide-Santiago de Chuco. - Lezama Leiva, Alexis Luis (2019)
This research work was carried out with the purpose of determining the prevalence of hepatic Fasciola in alpacas of the Huacaya race (Lama pacos), of different ages, which are located in the Chugurpampa sector of the Cahuide Peasant Community, district of Santiago de Chuco, province of Santiago de Chuco, region La Libertad; also, identify the degree of affectation and the economic losses caused. The diagnosis of this parasitosis was made by means of a parasitological examination in the laboratory, in order to determine the prevalence of eggs. It is concluded that there are no Fasciola hepatic eggs in the feces of the alpacas sampled within the scope of research; even though, eggs of Giardia lambia have been identified. To corroborate this assertion, it is recommended to carry out other research work, such as examining snails, grasses; post-morten diagnosis; immunodiagnostic examination, in order to determine the presence or not of Fasciola hepatic in other areas.